Pengembangan Media Video Animasi Tentang Pemahaman Kepemimpinan Siswa Di MTs Negeri 1 Yogyakrta - Wakhidatul Khoirunnisa; Ariadi Nurgraha (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
Students are the next generation of young people who need to be given an understanding of leadership in order to have an attitude of responsibility and be able to contribute in responding to future challenges. Through the services provided by BK teachers, the school becomes a forum for education and the formation of students' personalities and mentality. This study aims to develop animated video media about leadership as an effort to provide information about leadership to students at MTs Negeri 1 Yogyakarta. The research model used in this study adopts the Dick and Carry development model with the term ADDIE, which is a development model consisting of five stages including Analysis, Design, Development , Implementation, and Evaluation. The subjects in this study were 20 students who attended the student council at MTs Negeri 1 Yogyakarta. The results of the animated video media development research on leadership understanding based on the results of the Material Expert assessment, Media Expert assessment, and Service Expert assessment, all received the